2007
DOI: 10.2140/jomms.2007.2.2025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression of square honeycomb structures during underwater impulsive loading

Abstract: Significant reductions in the fluid structure interaction regulated transfer of impulse occur when sandwich panels with thin (light) front faces are impulsively loaded in water. A combined experimental and computational simulation approach has been used to investigate this phenomenon during the compression of honeycomb core sandwich panels. Square cell honeycomb panels with a core relative density of 5% have been fabricated from 304 stainless steel. Back supported panels have been dynamically loaded in through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Theoretical assessments indicate this beneficial effect arises from two phenomena: a reduction in the impulse acquired by the sandwich panel front face as a result of a fluid-structure interaction (FSI) effect [3,4,[8][9][10] and the higher flexural stiffness and strength of the sandwich. It has also been experimentally shown that the forces transmitted to supports when rigid back supported sandwich panels are impulsively loaded in water are significantly less than equivalent solid plates [11][12][13][14]. These reductions arise from a combination of beneficial FSI effects (which reduce the transmitted impulse) and a low core crushing stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical assessments indicate this beneficial effect arises from two phenomena: a reduction in the impulse acquired by the sandwich panel front face as a result of a fluid-structure interaction (FSI) effect [3,4,[8][9][10] and the higher flexural stiffness and strength of the sandwich. It has also been experimentally shown that the forces transmitted to supports when rigid back supported sandwich panels are impulsively loaded in water are significantly less than equivalent solid plates [11][12][13][14]. These reductions arise from a combination of beneficial FSI effects (which reduce the transmitted impulse) and a low core crushing stress.…”
Section: Introductionmentioning
confidence: 99%
“…After the beneficial FSI effect had been confirmed in water [2][3][4][5][6][7][8], numerous sandwich panel concepts for impulse and pressure mitigation have been explored [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…this case, the transmitted pressure is controlled by the dynamic crush strength of the core, σ cD . The required minimum thickness for the cellular core, h min , can be estimated from [Ashby et al 2000] and [Wadley et al 2007b] as…”
Section: Discussionmentioning
confidence: 99%
“…Vaziri and collaborators focused on metallic sandwich panels with different kinds of cellular cores such as hexagonal honeycombs [18], square honeycombs [19][20][21][22][23], open-cell rhombic dodecahedron cellular structures [24] and pyramidal truss cores [25][26][27][28], and explored some of their multifunctional applications, such as energy absorptions [27], sustaining shock loadings [19][20][21] and underwater impulsive loadings [22][23].…”
Section: Introductionmentioning
confidence: 99%